Pelatihan Jarimatika untuk Mengembangkan Kemampuan Berhitung Siswa Kelas Awal Sekolah Dasar di Purwakarta - Ahmad Rizal Jalaludin; Anggraeni Wishnu Ramadhianty; Nursela Dian Nursela Dian Patimah3; Novi Wulansari; Nurul Fitri Handini; Prisscillia Magdalena Putri; Wina Mustikaati; Neneng Sri Wulan; Indra Nugrahayu Taufik; Yupi Yuliawati (Indonesian Journal of Community Services in Engineering & Education (IJOCSEE), 2023)
This activity is motivated by the lack of numeracy skills of students. During the distance learning period, students' abilities were not honed due to less than optimal learning. Based on the results of observations at SDN 3 Nagri Tengah Purwakarta, many students in the early grades have not yet maximized their numeracy skills, especially in addition and subtraction. This service aims to develop numeracy skills for elementary students through the Jarimatika method. The method of implementing the activity includes three stages, namely planning, implementing and evaluating. The results of program implementation are (a) there is an increase in students 'numeracy skills, especially in terms of addition using the Jarimatika method with data analysis showing that before the intervention obtained a score of 30.0% then after the intervention obtained a score of 70.0%., (B) the students' ability to use Jarimatika method.